Feasibility of breast crawl in a tertiary care teaching institute - Gupta, Ashna; Prasad, Brijendra; Khadse, Sandhya; Valvi, Chhaya; Kulkarni, Rajesh; Rajput, Uday; Dawre, Rahul; Badjate, Priyanka; Kinikar, Arti (Indian Journal of Child Health, 2019)
Background: Early initiation of breastfeeding has many beneficial effects for both the mother and the baby. The breast crawl has been established as the ideal method for promoting early skin-to-skin contact and early initiation of breastfeeding. Objective: The objective of the study was to assess the feasibility of breast crawl in a busy tertiary care institute. Materials and Methods: An observational study was performed including 50 mother-baby pairs, admitted to the labor room of Sassoon General Hospital, Pune, from January 2018 for 6 months. Observations were made on patient and nurse attitude and behavior and were further analyzed. Results: Of the total subjects, 23 (46%) mothers had not received any counseling about breastfeeding during the antenatal period and none of them were familiar with the idea of breast crawl from the antenatal period. Of the 50 mothers, 27 mothers (54%) were concerned about privacy, 8 (16%) were concerned about environmental cold, 6 (12%) were worried about exposure, and 9 mothers (18%) were concerned about the baby, whereas 6 mothers (12%) had no concerns and 6 mothers had more than one concern. The attitude of the nursing staff was favorable (enthusiastic) 19 times, indifferent 23 times, reluctant 6 times, and unfavorable (uncooperative) 2 times. Conclusion: While it is highly desirable to implement breast crawl as a routine practice, there are several roadblocks such as lack of antenatal counseling, lack of awareness and motivation, lack of specific guidelines and instructions, skewed staff-to-patient and bed-to-patient ratio, and lack of privacy.